Cytomorphological Study of Lymphadenopathy at a Tertiary Health Care Hospital in Kathmandu (Nepal Medical College Journal, 2023)
Lymphadenopathy is most commonly encountered problems in clinical practice. Various etiological factors can cause lymphadenopathy. Cytomorphological study of lymphadenopathy is a window for diagnosis of many disease processes. Aspiration cytology provides a reliable, safe, rapid and economical method of screening the patients with accuracy. It can differentiate neoplastic from non-neoplastic lesions and therefore influences patient management preventing patient from being subjected to unnecessary surgery. Hospital based descriptive study was carried out in the Department of Pathology of a tertiary health care hospital in Kathmandu over a period of three years (1st June 2019 to 30th May 2022). A total of 331 cases of lymphadenopathy were included in the study. The aim of this study was to evaluate the cytomorphological findings of lymphadenopathy. Out of 331 cases of lymphadenopathy, 281 (84.9%) of the cases were non-neoplastic and 47 (14.2%) were neoplastic. Among non neoplastic lesions, reactive lymphadenitis 113 (34.1%) was the most common diagnosis followed by tubercular lymphadenitis, granulomatous lymphadenitis, suppurative lymphadenitis and necrotizing lymphadenitis. Among neoplastic, 40 (12%) were metastatic carcinoma and 7 (2.1%) were lymphoma. Among metastatic carcinoma the most common was squamous cell carcinoma followed by breast carcinoma, adenocarcinoma, papillary carcinoma of thyroid. Other metastatic carcinoma were small cell carcinoma of lung and melanoma. This study showed that cytomorphological study of lymph node is a convenient procedure for accurate assessment of patients with lymphadenopathy.